2022
DOI: 10.1111/jgh.15894
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of patients with autoimmune pancreatitis and inflammatory bowel disease: A systematic review and meta‐analysis

Abstract: Background and Aim Autoimmune pancreatitis (AIP) and inflammatory bowel disease (IBD) are categorized into immune‐mediated inflammatory disorders (IMIDs). While AIP is a pancreato‐biliary IMID with an increased incidence and prevalence among patients with IBD, its features are still unclear. This systematic review and meta‐analysis aims to assess the prevalence and clinical characteristics of AIP‐IBD patients. Methods Electronic databases were searched to identify observational studies assessing AIP and IBD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…In our study, the crude rate of AIP in IBD patients was 0.39%, compared to 0.57% in UC patients; previous studies in East Asia reported a crude rate of 0.40%–0.60% and 0.52%–0.54%, respectively 12–14 . Taken together, the prevalence of AIP in IBD patients is essentially similar in East Asia.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In our study, the crude rate of AIP in IBD patients was 0.39%, compared to 0.57% in UC patients; previous studies in East Asia reported a crude rate of 0.40%–0.60% and 0.52%–0.54%, respectively 12–14 . Taken together, the prevalence of AIP in IBD patients is essentially similar in East Asia.…”
Section: Discussionsupporting
confidence: 63%
“…In our study, the crude rate of AIP in IBD patients was 0.39%, compared to 0.57% in UC patients; previous studies in East Asia reported a crude rate of 0.40%-0.60% and 0.52%-0.54%, respectively. [12][13][14] Taken together, the prevalence of AIP in IBD patients is essentially similar in East Asia. On the other side, the crude rate of IBD was 2.91% in patients with AIP and 36.67% in patients with type 2 AIP, which are lower than previously reported (5.6%-29.4% and 42.9%-58.3%, respectively).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The association between AIP and IBD is well established, particularly between UC and type 2 AIP ( 52 55 ). The prevalence of IBD is significantly higher in patients with AIP (approximately 11%–30%) ( 54 , 56 , 57 ). Approximately 30%–48% of type 2 AIP cases are associated with IBD ( 9 , 58 , 59 ).…”
Section: Prevalence Of Type 2 Aip–ucmentioning
confidence: 99%